GRI Index 2020 - World Bank (World Bank, Washington, DC, 2020)
This 2020 World Bank GRI Index is an inventory of the sustainability considerations used in World Bank lending and analytical services, as well as within its corporate practices. This sustainability disclosure index has been prepared in accordance with the Core option of the GRI Standards1. The GRI Index covers activities carried out during fiscal year 2020, from July 1, 2019 through June 30, 2020. The COVID-19 pandemic impacted the World Bank’s operations and staff activities through reduced travel, the extended shutdown of our offices, and a shift in staff health services. Where significant, these impacts have been noted in the report.